Vigor de sementes e desempenho de campo de arroz híbrido - Neves, Márcio Blanco das (2010)
The aim of this study was to evaluate the effect of seed vigor on hybrid rice plant performance, grown in communities consisting of different combinations of plants originated from different vigor levels seeds along the line of seeding, individually or in arrangements of plants. Two experiments were conducted at the Experimental and Didactic Plant Science Department, Faculty of Agronomy "Eliseu Maciel . Two batches of hybrid rice seed from the RiceTec Company, Avaxi CL ®, characterized as high and low vigor were used for this aim. The first experiment evaluated the effect of seed vigor on the behavior of individually analyzed plants grown at different population densities. It was tested three different arrangements of plants: exclusive plants from high vigor seeds, exclusive plants from low vigor seeds, and half plants from high vigor seeds interspersed with half of plants from low vigor seeds. The arrangements were distributed in two densities: 125 plants per square meter and 63 plants per square meter. In the second study, the rice plants had their behavior evaluated individually within the community, and also, the general behavior of the community, formed by arrangements of plants from high and low vigor seeds in accordance the ratio of 100:0, 75:25, 50:50, 25:75, 0:100 interspersed plants, contiguous along the line of seeding. It was conducted five different arrangements of plants originated from high and low vigor seeds with 0.2 m spacing between the lines and 125 plants per square meter of population density. Plants were obtained by sowing in the field plots, located near the experiments site, sown 0,025 m deep and then transplanted to the field trial. In conclusion, plants originated from high vigor seeds, in hybrid rice, have higher performance than plants from low vigor, within communities. Population density did not influence the results of height, number grains per panicle, 1000 grains weight and harvest index, however was distinguishing factor for the other characters analyzed. Increases in the proportion of plants originated from high vigor seeds provided improvement in yield components and communities productivity. Established plant communities with high vigor seed showed grain yield 20% higher than the communities of plants from low vigor seeds. Due to higher performance in the evaluated parameters, there is evidence of dominance effect of plants from high vigor seeds over the plants from low vigor seeds, in the communities.